Toward the Archival Multiverse: Challenging the Binary Opposition of the Personal and Corporate Archive in Modern Archival Theory and Practice - McKemmish, Sue; Piggott, Michael (Archivaria, 2013)
This article points to the binary oppositions that characterize modern archival theory and much practice in the English-speaking archival world, with particular reference to the way they are manifest in the Australian context. At a time when mergers of library and archives institutions are increasingly an option, it is appropriate to consider in particular the impact of the binary construct of the manuscripts tradition in libraries on the one hand, and the focus of most national and state archives on government records on the other. In this article, we challenge the binary opposition of the personal and corporate archive, drawing on records continuum, postmodern, and postcustodial archival theory as developed in Australia and elsewhere; Indigenous ways of knowing; and emergent thinking on co-creation, the multiple simultaneous provenance of records, and the archival multiverse. We point to the need for archival research and theory building relating to the plurality of personal and corporate recordkeeping behaviours and cultures in the context of the complex interrelationships between “evidence of me” and “evidence of us” in the continuum, and in the online cultures and shared spaces of our digital worlds. We conclude with some suggestions about the rich possibilities for further research on personal recordkeeping in these contexts. RÉSUMÉ Cet article montre les oppositions binaires qui caractérisent la théorie archivistique moderne et plusieurs pratiques professionnelles dans le monde archivistique anglophone, en se penchant surtout sur la façon dont elles se manifestent dans le contexte australien. À une époque quand les amalgamations des bibliothèques et des archives deviennent de plus en plus communes, il importe de considérer en particulier l’impact d’une construction binaire spécifique : d’un côté, la tradition manuscrite dans les bibliothèques, et de l’autre, l’accent placé par la plupart des archives nationales et étatiques sur les archives gouvernementales. Dans cet article, nous contestons l’opposition binaire des archives personnelles et corporatives, en nous inspirant du continuum des documents d’archives, des théories archivistiques postmodernes et des théories allant au-delà de la théorie traditionnelle de la garde des documents (« post-custodial ») développées en Australie et ailleurs, les façons autochtones de savoir, et les pensées émergentes autour de la co-création, de la provenance multiple et simultanée des documents d’archives, et de multivers archivistiques. Nous montrons le besoin de recherche en archivistique et en construction de la théorie qui sont liées à la pluralité des pratiques et des cultures de gestion des documents d’archives personnelles et corporatives, dans un contexte d’interdépendances complexes entre « la preuve du moi » et « la preuve du nous » dans ce continuum, et dans les cultures en ligne et les espaces partagés de nos mondes numériques. En conclusion, nous offrons quelques suggestions par rapport aux excellentes possibilités de recherches plus poussées en gestion des documents privés dans ces contextes.